2014
DOI: 10.4103/0973-6247.137438
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization and autoimmunization in transfusion dependent thalassemia major patients: Study on 319 patients

Abstract: Background:The development of anti-red blood cell antibodies (both allo-and autoantibodies) remains a major problem in thalassemia major patients. We studied the frequency of red blood cell (RBC) alloimmunization and autoimmunization among thalassemia patients who received regular transfusions at our center and analyzed the factors, which may be responsible for development of these antibodies.Materials and Methods:The study was carried out on 319 multiply transfused patients with β-thalassemia major registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 28 publications
15
52
1
Order By: Relevance
“…This finding is supported by some of the earlier studies done by Alick et al, Dhawan et al, Vishinski E et al & Jensen LS et al who have found a strong correlation between the numbers of blood units transfused and alloantibody formation. [11,14,20,22] CONCLUSION: By considering the results of present and other reference Indian studies, blood banks of India should go for universal type and screen policy for finding the prevalence of alloantibodies in general patient and donor population. The indigenous development of local cell panels would be a better option to ensure adequate supplies of reagent red cells and introduction of type and screen policy for all the patients.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This finding is supported by some of the earlier studies done by Alick et al, Dhawan et al, Vishinski E et al & Jensen LS et al who have found a strong correlation between the numbers of blood units transfused and alloantibody formation. [11,14,20,22] CONCLUSION: By considering the results of present and other reference Indian studies, blood banks of India should go for universal type and screen policy for finding the prevalence of alloantibodies in general patient and donor population. The indigenous development of local cell panels would be a better option to ensure adequate supplies of reagent red cells and introduction of type and screen policy for all the patients.…”
Section: Discussionmentioning
confidence: 84%
“…[11,18,19] Anti c was detected in four patients, Anti-D in four, Anti-N in three, anti-C in two and Anti-M, Anti e in one patient each. Anti-c and anti-D (27%) were the most common antibodies in our study, which is comparable to Thakral et al (38.8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, when annual transfusion requirement rises above 200 ml/kg/y of pure red cells, splenectomy is one of several strategies to reduce the rate of iron-loading [2]. Splenectomy leads to a higher prevalence of autoantibodies [9]. Whether splenectomy has a bearing on the outcome of allogeneic stem-cell transplantation in patients with TM is not well-defined [10].…”
mentioning
confidence: 99%